Bioinspired damage tolerant diamond-metal laminates by alternating CVD and PVD processes. (January 2022) - Fromm, Timo; Bruns, Sebastian; Müller, Marie-Christin; Fink, Alexander; Borchardt, Rudolf; Rosiwal, Stefan M.; Durst, Karsten
Graphical abstract: Highlights: Successive HCVD and PVD processes were used to produce diamond-metal laminates with up to ten layers of diamond. This approach allows precise control of layer thicknesses and both diamond and metal layers are of uniform thicknesses. The diamond-metal laminates outperform other ceramic-metal composites in terms of strength with values ranging from 1250 MPa up to 2250 MPa. By implementing a laser structuring of diamond layers, a diamond-based, biomimetic brick-and-mortar structure was realized, exhibiting a damage tolerant behavior. Abstract: In this study, we present a novel process to fabricate diamond-metal laminates. By means of successive chemical vapor deposition and physical vapor deposition processes, the lamellar material is deposited layer by layer on silicon wafers. Laminates consisting of two, five and ten layers of diamond were realized. In addition, fabrication of diamond-based, biomimetic brick-and-mortar structures was successful for the first time. For this purpose, diamond layers of a five-layer laminate were structured by laser cutting into hexagonal platelets with diameters of 400 µm and 800 µm. The mechanical behavior was characterized by three-point bending. Mostly spontaneous failure with little crack deflection was observed, indicating a strong diamond-metal interface. At over 1250 MPa, the laminates exhibit nominal strengths that exceed those of other lamellar ceramic-metal composites by at least a factor of two, while fracture energy lies in a medium range. The laminates with segmented diamond layers exhibit damage tolerance.